Computational Fluid Dynamics Prediction of the Sea-Keeping Behavior of High-Speed Unmanned Surface Vehicles Under the Coastal Intersecting Waves - Xiaobin Hong; Guihong Zheng; Ruimou Cai; Yuanming Chen; Guoquan Xiao (Journal of Marine Science and Engineering)
To better study the sea-keeping response behavior of unmanned surface vehicles (USVs) in coastal intersecting waves, a prediction is conducted using the CFD method in this paper, in which a USV with the shape of a small-scale catamaran and designed target for high-speed navigating is considered. The CFD method is proved to be good enough at ship response prediction and can be utilized in abundant forms of towing experiment simulations, including planar motion mechanism experiments. The regular and irregular wave generation of numerical CFD can also virtualize the actual wave tank work, making it equally scientific but more efficient than the real test. This research regards the changing trend of encounter characteristics of USVs meeting two trains of waves with different inclination angles and wavelengths by monitoring wave profiles, pitch, heave, acceleration, slamming force, and pressure on specific locations of the USV hull. This paper first introduces the modeling method of intersecting waves in a virtual tank and verifies the wave profiles by comparing them with a theoretical solution. Further, the paper focuses on the sea-keeping motion of USVs and analyzes the complicated influences of encounter parameters. Eventually, this paper analyzes the changing pattern of the motion in encounter frequency and investigates the severity during the sea-keeping period through acceleration analysis.